Microvariation in the division of labor between null- and overt-subject pronouns: the case of Italian and Spanish - Contemori, Carla; Di Domenico, Elisa (Applied psycholinguistics, 2021)
In Italian, null pronouns are typically interpreted toward antecedents in a prominent syntactic position, whereas overt pronouns prefer antecedents in lower positions. Interpretation preferences in Spanish are less clear. While comprehension and production have never been systematically compared in Italian and Spanish, here we look at the preferences for overt- and null-subject pronouns in the two languages using the same production and comprehension materials. Using an offline comprehension task with a group of Spanish and Italian speakers, we tested sentences where the type of pronoun (null vs. explicit) and position of the pronoun (anaphoric vs. cataphoric) are manipulated, to determine how context affects speakers’ interpretations in the two languages. With two production tasks, we measured referential choice in controlled discourse contexts, linking the production patterns to the differences observed in comprehension. Our results indicate microvariation in the two null-subject languages, with Spanish following the Position of Antecedent Hypothesis but to a lesser degree than Italian. More specifically, in Spanish, the weaker object bias for overt pronouns parallels with a higher use of overt pronouns (and with fewer null pronouns) in contexts of topic maintenance.